Bibliometric Analysis of Chemistry Publication Trends on Scopus in The Era of Big Data - Bakti, Andi Budi (Indonesian Journal of Chemical Science, 2024)
In the 21st century, chemistry has seen a major shift in data management practices. Analyzing research trends is crucial for maintaining relevance and innovation. This study aims to: (1) identify the contributions of researchers and institutions and assess their impact; (2) map the network of interactions among publications, references, topics, researchers, and institutions; and (3) predict future directions and recommend research opportunities in chemistry. This study employs bibliometric analysis and science mapping techniques with VOSviewer. The study finds that: (1) J. M. Cole and the United States are the leading contributors; (2) big data research in chemistry is not yet deeply and continuously explored, with researchers often working in small groups and focusing on topics such as "machine learning," "chemometrics," "cheminformatics," and "deep learning"; and (3) "data mining" is underexplored, presenting new research opportunities and directions for chemistry in the era of big data.